Desain Rancang Bangun Pelubang Tanah untuk Biopori Berbasis Sensor Ultrasonic - Riandara, Hervianna Indira Kusuma; Manalu, Helena Wilhelmina; Khadavy, Muhammad Firdaus (Civil Infrastructure Engineering and Architectural Design, 2024)
residents. Soil that is no longer able to absorb water will result in water accumulation, which then forms puddles known as floods. Insufficient infiltration holes are one of the factors contributing to floods. Biopores can serve as an alternative flood prevention method, as they facilitate water absorption into the soil while also being conducive to compost production. The objective of this research is to design a soil drilling tool for biopores as part of flood prevention efforts. An ultrasonic sensor-based soil drilling tool for biopores offers an innovative solution to address flood-related issues. Ultrasonic sensors are utilized to accurately determine the appropriate depth for creating biopores. This is crucial because biopores created at incorrect depths may not function optimally in channeling water into the soil. Ultrasonic sensors enable precise measurement of soil depth without the need for manual excavation. This allows users of the tool to identify ideal locations for biopore creation without causing excessive environmental damage to the surrounding area.